2021
DOI: 10.1109/access.2021.3087345
|View full text |Cite
|
Sign up to set email alerts
|

Energy Production Forecasting From Solar Photovoltaic Plants Based on Meteorological Parameters for Qassim Region, Saudi Arabia

Abstract: Due to the increasing cost of crude oil because of pandemic COVID-19 and global environmental threats, the exploitation of fossil fuels for power generation is discouraged. Further, the demand for electrical power is increasing drastically, and therefore, the exploitation of renewable energy resources, particularly solar photovoltaic-based technology for power generation is invigorated. However, the large-scale penetration of solar photovoltaic is becoming a major challenge in terms of stability, reliability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In this work, major environmental parameters which directly influence PV power generation have been considered. To validate our analysis of features and their importance in predictions, it has been shown that the power generation calculated using certain environmental parameters by [36] is close to actual power generated. The various 4 and Table 5.…”
Section: Impact Of Meteorological Parameters On Solar Pv Power Genera...mentioning
confidence: 89%
See 1 more Smart Citation
“…In this work, major environmental parameters which directly influence PV power generation have been considered. To validate our analysis of features and their importance in predictions, it has been shown that the power generation calculated using certain environmental parameters by [36] is close to actual power generated. The various 4 and Table 5.…”
Section: Impact Of Meteorological Parameters On Solar Pv Power Genera...mentioning
confidence: 89%
“…In Table 6, a random sample range of 20 observations of power generation calculated using DR_Avg and WS_Avg and actual power has been tabulated. Using this method [36] a root mean squared error (RMSE) of 799.25 is observed against the actual power generated. Hence choice of environmental parameters heavily affects the results.…”
Section: Impact Of Meteorological Parameters On Solar Pv Power Genera...mentioning
confidence: 99%
“…In the spot market, the intraday market will gradually play a more important role and balance the transaction volume in the market in real time. will increase, and at the same time, the volatility of the electricity spot market clearing price will increase [18][19].…”
Section: Key Issues Of Constructionmentioning
confidence: 99%
“…In addition, ensemble learning, as a kind of shallow learning, has received extensive attention in recent years. Common ensemble learning includes extreme gradient boosting (XGBoost) (Li et al, 2022), ensemble trees (Alaraj et al, 2021), random forest (RF) (Kumar and Thenmozhi, 2006), LGBM (Wang Y et al, 2020), and CatBoost (Prokhorenkova et al, 2018). In (Li et al, 2022), the authors propose a prediction model of solar irradiance based on XGBoost.…”
mentioning
confidence: 99%
“…In (Li et al, 2022), the authors propose a prediction model of solar irradiance based on XGBoost. In (Alaraj et al, 2021), the ensemble trees based machine learning approach considering various meteorological parameters is proposed for PV power forecasting. However, with the development of big data technology and intelligence optimization theories in recent years, the drawback of shallow learning models will be prone to the curse of dimensionality and under-fitting, which makes it difficult to forecast PV power data in a big data era (Soares et al, 2016).…”
mentioning
confidence: 99%